New water footprint indicators for urban water cycle - Varriale, Rossana (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The Water Footprint - WF is an indicator of anthropogenic pressures on aquatic systems. It is widespread and scholars have developed numerous insights into the virtual water flux activated by the global trade in agricultural and livestock products. In this study the flow of water resources that crosses the urban territories is reviewed through some contributions by researchers of WF and Urban Metabolism. Two new indicators are then developed to measure the phases of the anthropogenic cycle of water, starting from urban consumption. These indicators were then used to measure the urban footprint in Italy calculated as: drinking water consumption and volumes lost due to waterproofing of urban land. The total value of the blueprint of Italian municipalities is estimated at UBW = 5.184ml / m3 / year, while the green footprint is UGW = 1.123.860 ml / m3 / year. The calculation method is proposed so that it can be a useful tool for planners to identify the types of water use in urban areas to develop an bottom up approach.